Therapeutic exercise in Abdominal Hernioplasty: physio-cellular mechanisms and translational protocols for recurrence reduction (2014-2024) (Revisión ) (Revista científica Olimpia, 2025)
This article summarizes the scientific evidence (2014-2024) on the physiological mechanisms of therapeutic exercise in postoperative recovery from abdominal hernias, with the aim of establishing a translational framework that integrates biomechanics, cell biology, and technology to optimize rehabilitation protocols. The justification arises from the persistent recurrence rates (10-25%) associated with traditional approaches based on prolonged rest, despite advances in minimally invasive surgical techniques and biomaterials. The historical and trend evolution section (2014-2024) analyzes the transition from passive protocols to the early integration of exercise, highlighting milestones such as the validation of prehabilitation and early neuromuscular activation (2-4 weeks postoperatively), which reduce recurrences by 40%. This analysis contextualizes the urgency of standardizing evidence-based physical interventions. Under the heading of physiological mechanisms, cellular responses to exercise are broken down: tissue remodeling, intra-abdominal pressure regulation, angiogenesis, and immune modulation.These fundamentals explain why exercise accelerates functional recovery and prevents complications. The section on stepped protocols proposes a three-phase model (acute, strengthening, recovery), supported by biomarkers and parameters. This section is crucial for translating pathophysiological evidence into guidelines applicable by rehabilitation professionals. Finally, technological challenges and solutions (telerehabilitation, wearables for monitoring intra-abdominal pressure) are addressed, highlighting the need to close access gaps and personalize therapies. The article concludes that the integration of these axes will transform therapeutic exercise into the gold standard for post-hernioplasty recovery, reducing recurrences and improving quality of life.
Keywords: Therapeutic exercise, abdominal hernia, pathophysiology, surgical repair, recurrence, rehabilitation.